Numerical Priming Between Touch and Vision Depends on Tactile Discrimination. (January 2016) - Faivre, Nathan; Salomon, Roy; Vuillaume, Laurène; Blanke, Olaf
Although the interaction between vision and touch is of crucial importance for perceptual and bodily self-consciousness, only little is known regarding the link between conscious access and tactile processing. Here, we tested whether the numerical encoding of tactile stimuli depends on conscious discrimination. On each trial, participants received between zero and three taps at low, medium, or high intensity and had to enumerate the number of visual items subsequently presented as a visual target. We measured tactovisual numerical priming, that is, the modulation of reaction times according to the numerical distance between the visual target and tactile prime values. While numerical priming and repetition priming were respectively elicited by high and medium intensity stimuli, no effect was found for low intensity stimuli that were not discriminable. This suggests that numerical priming between touch and vision depends on tactile discrimination. We discuss our results considering recent advances in unconscious visual numerical priming.